2011
DOI: 10.1590/s1676-06032011000300015
|View full text |Cite
|
Sign up to set email alerts
|

Anurans of a riparian forest in Sao Carlos, state of Sao Paulo, Brazil

Abstract: Abstract:We surveyed anuran amphibians in a riparian forest fragment of the Córrego do Espraiado, located at the Universidade Federal de São Carlos, Municipality of São Carlos, state of São Paulo, southeastern Brazil. During March 2009 and February 2010 we did weekly surveys in which we recorded 13 anuran species. The species showed a seasonal reproductive activity. In addition, we found a positive correlation between the number of reproductively active species and photoperiod. We also found that the studied c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…auratus and Leptodactylus latrans has not been evaluated due to lack of more precise identification of the former and a recent taxonomic revision of the group to which the latter belongs (Lavilla et al 2010). By analyzing the geographical distribution, reproductive modes, and use of the environment for breeding activity, the only observable patterns in the community under study are that (1) for both widely distributed species and species of more restricted distribution, reproductive mode 1 (eggs and exotrophic tadpoles in lentic water) was the most common, as observed in other studies of Neotropical communities (Zimmerman and Simberloff 1996;Zina et al 2007;Camurugi et al 2010); (2) reproductive modes involving foam nests were typically observed in species that occupied temporary environments, as also observed for other anuran communities (Vieira et al 2007;Kopp et al 2010); and (3) the only species with direct development (Haddadus binotatus) was recorded in breeding activity only in the interior of the fragment, which also corroborates the data available in the literature (Canedo and Rickli 2006;Camurugi et al 2010;Sabbag and Zina 2011). Thus, apparently, the reproductive modes did not determine the range of the geographic distributions but is strongly related to the occupation of a particular type of breeding site and may determine the spatial distribution of the species, as in the two cases mentioned above.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…auratus and Leptodactylus latrans has not been evaluated due to lack of more precise identification of the former and a recent taxonomic revision of the group to which the latter belongs (Lavilla et al 2010). By analyzing the geographical distribution, reproductive modes, and use of the environment for breeding activity, the only observable patterns in the community under study are that (1) for both widely distributed species and species of more restricted distribution, reproductive mode 1 (eggs and exotrophic tadpoles in lentic water) was the most common, as observed in other studies of Neotropical communities (Zimmerman and Simberloff 1996;Zina et al 2007;Camurugi et al 2010); (2) reproductive modes involving foam nests were typically observed in species that occupied temporary environments, as also observed for other anuran communities (Vieira et al 2007;Kopp et al 2010); and (3) the only species with direct development (Haddadus binotatus) was recorded in breeding activity only in the interior of the fragment, which also corroborates the data available in the literature (Canedo and Rickli 2006;Camurugi et al 2010;Sabbag and Zina 2011). Thus, apparently, the reproductive modes did not determine the range of the geographic distributions but is strongly related to the occupation of a particular type of breeding site and may determine the spatial distribution of the species, as in the two cases mentioned above.…”
Section: Resultssupporting
confidence: 88%
“…The fauna of these domains and transition areas is still insufficiently sampled and anthropogenic changes that modify the structure of the landscape are a threat to the local taxa, especially those which have been poorly studied or are as yet unknown. The scarcity of studies in transitional environments is probably related to the fact that few transitional areas are protected and most of them have been and still are subject to impacts caused by human activities (Sabbag and Zina 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As stated by Zanella (2011), the evolutionary history of the Caatinga, Cerrado and Chaco could be independent, since the endemic patterns for each of these regions have specific characteristics (Morrone 2014). However, in transition zones, multiple factors can cause the differentiation of community composition (Kark et al 2007, Vasconcelos et al 2010, Sabbag & Zina 2011 we hypothesized that anuran species richness and the number of reproductive modes from different Brazilian localities vary according to climatic and altitudinal variables. Published data were compiled from 36 Brazilian localities and climatic and altitudinal data were extracted from an available database.…”
Section: Discussionmentioning
confidence: 90%
“…Rather, SDM methods consequently provided only those suitable areas where H. caingua would be able to occupy. Then, other factors than climate might be also responsible in the current distribution of H. caingua, since well surveyed sites between the current records, which have higher probabilities of occurrence according to the species distribution modelling, have no occurrence record for this species (e.g., Bernarde and Machado, 2001;Vasconcelos and Rossa-Feres, 2008;Serafim et al, 2008;Santos et al, 2009;Armstrong and Conte, 2010;Conte et al, 2010;Forlani et al, 2010;Silva and RossaFeres, 2011;Sabbag and Zina, 2011). We believe that further studies on natural history, populations' genetic structure and geographic distribution models implementing other factors than climate will be important to elucidate some ecological and evolutionary aspects of the distribution of H. caingua in South America.…”
Section: Discussionmentioning
confidence: 99%